MULTIDISCIPLINARY APPROACH OF IMPACTED PERMANENT MAXILLARY LEFT CENTRAL INCISOR AND CANINE - Yustisia Puspitasari; Jusuf Sjamsudin (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACT Background: The permanent maxillary canines have significant incidence of impaction, being the most affected teeth after the third molars, while impacted maxillary insicor is the third most commonly impacted tooth. Objective: This case report is about a multidisclipinary orthodontic treatment of 12 years old female with chief complaint of unerupted anterior upper teeth. Case: A case with unerupted of permanent maxillary left central incisor tooth and permanent maxillary left canine tooth, with Angle Class 1 molar relation and crowded of mandibular teeth. Panoramic and occlusal radiograph showed impacted 21 tooth with severely root dilacerations and impacted 23 tooth in palatal and horizontal position. Case Management: The patient was treated with Edgewise technique. Surgical approach was applied 3 months after levelling and unravelling stage to extract 21 tooth due to its severely root dilaceration and to bond lingual button on palatal side of 23 tooth. Orthodontic traction of impacted 23 tooth was applied a week after being exposed to the position of 21 tooth. Thirteen months after traction, 23 tooth was totally erupted and need 8 additional months to reach its final position. The crown of 23 was reshaped with porcelain fused to metal crown and 63 tooth was left still and got conservative treatment with composite. Conclusion: Orthodontic traction and reshaping of impacted 23 tooth was succeeded to replace the position of 21 tooth with good occlusion and esthetic. Based on OPG after treatment, all teeth were in good root paralleling. The patient was satisfied with good occlusion and esthetic. Keywords: Impacted maxillary canine, Impacted maxillary incisor, Root dilaceration, Orthodontic treatment, Surgical exposure